2017
DOI: 10.1111/coa.12904
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis in anticoagulated patients: Fewer hospital admissions and shorter hospital stays on rivaroxaban compared to phenprocoumon

Abstract: Objectives: Treatment of epistaxis in patients on anticoagulants is challenging and associated with higher admission rates and longer hospital stays compared with patients without anticoagulation. However, there is little information about epistaxis in patients taking new direct oral anticoagulants such as rivaroxaban compared with patients on traditional vitamin K antagonists such as phenprocoumon.Design: Retrospective cohort study. This is an open access article under the terms of the Creative Commons Attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 11 publications
3
48
3
2
Order By: Relevance
“…As regards outcome parameters, there were no differences between the group with respect to the number of hospital admissions and length of hospitalisation. Real-life data, also including economical considerations in connection with bleeding events, are emerging on anticoagulation and the newer DOACs [15]. Those studies may influence the choice of a specific anticoagulant medication.…”
Section: Discussionmentioning
confidence: 99%
“…As regards outcome parameters, there were no differences between the group with respect to the number of hospital admissions and length of hospitalisation. Real-life data, also including economical considerations in connection with bleeding events, are emerging on anticoagulation and the newer DOACs [15]. Those studies may influence the choice of a specific anticoagulant medication.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital stay was longer for dabigatran patients, however, because the lack of an easily available coagulation test and persistent oozing after removal of packing made it necessary to keep the patients under continued observation (25). One retrospective study of epistaxis in patients taking rivaroxaban showed a lower percentage of inpatient admissions (10.4% versus 18.0%, p = 0.033) and shorter hospital stay (0.7 ± 2.2 versus 1.5 ± 3.7 days, p = 0.011) in comparison to patients taking vitamin K antagonists (26). Another risk factor identified was alcohol (14)(15)(16).…”
Section: Contamination Controlmentioning
confidence: 99%
“…A number of drugs such as warfarin, dipyridamole, rivaroxaban, and nonsteroidal anti-inflammatory drugs (NSAIDs) can affect blood coagulation [1,29,40,68]. NSAIDs, including aspirin and ibuprofen, are the most common drugs that may interfere with coagulation [45]; however, researchers have yet to establish a definitive causal association between the use of NSAIDs and epistaxis [69][70][71].…”
Section: Reviewmentioning
confidence: 99%
“…It has been estimated that 24% to 33% of patients admitted for nosebleeds are taking anticoagulants or antiplatelet medications [2]. Vitamin K antagonists, such as phenprocoumon, have also been shown to contribute to recurrent epistaxis [68,72]. It has been reported that specific serotonin reuptake inhibitors and antibiotics can induce epistaxis; however, most of those bleeding episodes are mild and easily reversed [1].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation